Reproductive outcomes and risk factors of women with septate uterus after hysteroscopic metroplasty - Chang, Yanan; Shen, Minghong; Wang, Sha; Guo, Zhengchen; Duan, Hua (Frontiers in Endocrinology, 2023)
Background: Hysteroscopic metroplasty of the uterine septum has been the standard treatment strategy to improve reproductive outcomes, but there are still controversies about the appropriateness of metroplasty. In addition, there have been few studies of the factors related to reproductive outcomes of women after surgery. The study aimed to evaluate the reproductive outcomes and the associated risk factors that influence reproductive outcomes after hysteroscopic metroplasty of women with septate uterus and the desire to conceive. Methods: This study was an observational study. Cases were screened by searching electronic patient files, and demographic factors were collected. We conducted telephone follow-ups to collect the postoperative reproductive outcomes. The primary outcome of this study was live birth, and secondary outcomes were ongoing pregnancy, clinical pregnancy, miscarriage, and preterm birth. Demographic variables included patients’ age, body mass index (BMI), the type of septum, infertility and miscarriage history, and complications including intrauterine adhesions, endometrial polyps, endometriosis, and adenomyosis were collected to perform univariate and multivariate analyses to predict the risk factors of reproductive outcomes after surgery treatment. Results: In total, 348 women were evaluated and followed up. There were 95 cases (27.3%, 95/348) with combined infertility, 195 cases (56.0%, 195/348) with miscarriage history, and cases combined with intrauterine adhesions, endometrial polyps, endometriosis, and adenomyosis were 107 (30.7%, 107/348), 53 (15.2%, 53/348), 28 (8.0%, 28/348), and 5 (1.4%), respectively. Following surgery, the live birth rate and clinical pregnancy rate were significantly higher than for prior to surgery (84.6% vs 3.7%, p= 0.000; and 78.2% vs 69.5%, p= 0.01, respectively), miscarriage rate and preterm delivery rate were significantly lower (8.8% vs 80.6%, p= 0.000; and 7.0% vs 66.7%, p=0.000, respectively). Miscarriage history, and complications, multivariable logistic regression analysis revealed age ≥ 35 years and primary infertility as independent factors that affected postoperative clinical pregnancy (OR 4.025, 95% CI 2.063–7.851; and OR 3.603, 95% CI 1.903–6.820; respectively) and ongoing pregnancy (OR 3.420, 95% CI 1.812–6.455; and OR 2.586, 95% CI 1.419–4.712; respectively). Conclusions: Hysteroscopic metroplasty could lead to improved reproductive outcomes of women with septate uterus. Both age and primary infertility were independent factors for postoperative reproductive outcomes.